The Effect of Public Debt on Domestic Product and Unemployment (An Empirical Study on the Palestinian Economy) - Sweis, Khalid Mohammad Hasan; Sabri, Tamer Bahjat Hussain (International Journal of Business, Economics and Management, 2016)
This study sought to recognize the effect of public debt on unemployment and domestic product. Also, it aimed to identify the developments that occurred in some indices in the Palestinian economy. To achieve the goals of this study, the researchers employed the data covering the period (1999-2014) as well as the simple regression analysis. The findings showed that the percentage of public debt to gross domestic product amounted, on average, by 20%. Furthermore, it was found that there is a connection of statistical effect between the rate of public debt and the independent variable, rate of debt, to gross domestic product. Meanwhile, the findings showed no connection between the rate of public debt and gross domestic product.